EP1349 Conservative management of a clear cell vaginal adenocarcinoma with laparoscopic staging, ovarian transposition, and brachytherapy. (1st November 2019) - Protopapas, A; Vlachos, DE; Vlachos, G; Sotiropoulou, M; Sarris, K; Terzi, M; Loutradis, D
Abstract : Introduction/Background: Clear cell adenocarcinomas (CCA) of the lower genital tract associated or not to previous in utero diethylstilbestrol exposure, are very rare tumors. Such a diagnosis in a young and nulliparous woman poses difficult dilemmas regarding treatment. Conservative management with preservation of fertility may be an option in carefully selected patients offering good results in terms of survival rates, giving a chance to achieve a pregnancy. Methodology: A 24 years old nulliparous patient presented with irregular vaginal bleeding from a solitary 2 cm upper third exophytic vaginal lesion. Histology of colposcopically directed biopsies revealed the presence of a grade 2 CCA. Subsequent hysteroscopic examination showed a normal uterine cavity with open tubal ostia. Endometrial biopsy was negative and the preoperative evaluation was unremarkable for metastatic disease. The patient was managed with laparoscopic staging including systematic pelvic lymphadenectomy plus infracolic omentectomy, and bilateral ovarian transposition with tubal conservation, followed by vaginal brachytherapy. Results: The procedure was carried out without any intraoperative complications. Ovaries were transposed outside the pelvis, and tubes were suspended separately with non-absorbable sutures for future reconstruction. Twenty pelvic lymph nodes were excised. All specimens were negative for metastatic disease. The patient made an uneventful postoperative recovery, and concluded brachytherapy with complete disappearance of the vaginal lesion. Six years after the initial treatment the patient is without evidence of disease. Conclusion: Vaginal CCA remains a rare malignancy of the urogenital tract, occurring mainly in young women with in utero exposure to diethylstilbestrol or history of vaginal endometriosis. Our experience agrees with the international literature, that conservative treatment of early stage disease is oncologically safe and the fertility of these young patients can be spared. Disclosure: Nothing to disclose